ASSESSMENT OF EXCHANGE RATE INSTABILITY AND SMALL AND MEDIUM SCALE AGRICULTURAL BUSINESSES ACTIVITIES IN NIGERIA - Ime Robson Nseobot; Udongwo, Iboro Ibanga; Akang, Akaninyene Udo (Journal Park Publishing, 2022)
The study examined the assessment of exchange rate instability and small and medium scale agricultural businesses in Nigeria. The research design for this study is an Expost Facto design. The population of the study consisted of consisted of small scale agricultural businesses in the North East senatorial district of Akwa Ibom State. Simple random sampling technique was used to select 379 respondents out of the population. The instrument used for data collection was questionnaire. The instrument was validated by two experts in Test and Measurement. Crombach Alpha reliability technique was used for testing the reliability of the instrument and reliability index of .91 was realized, hence the instrument was regard as being reliable. Data from completed questionnaires was subjected to regression analysis. The findings showed and concluded that there is significant effect of exchange rate instability on the performance of small and medium scale timber business in South-South Nigeria. The significance of this result is in the agreement with the opinion of Black (2003) an exchange rate system can also be fixed or allowed to fluctuate. A fixed exchange rate is a system in which a country’s exchange rate remains constant or stays within some small margin of fluctuation around a constant par value. On the other hand, the floating exchange rate (which is our concern in this study) is an exchange rate system with no government or central bank action to keep it stable. The study recommended that agricultural businesses should be seen by all as a panacea for high productivity. Hence, it should be practiced by all sectors of SMEs in order to quickly fast track and meet up with the objectives of the organization.
Keywords: exchange rate instability; gricultural businesses; floating exchange rate